Phenotypic expression of mutations in a wide-host-range R plasmid in Escherichia coli and Rhizobium meliloti. - Hooykaas, P J (1982)
Eight different derivatives of R plasmid RP1 with thermosensitive mutations affecting maintenance in Escherichia coli and Pseudomonas aeruginosa were introduce into Rhizobium meliloti. None of the plasmids showed a thermosensitive character in R. meliloti. On the other hand, a certain deletion mutation in RP1 was found to cause plasmid instability in rhizobia and agrobacteria, but not in E. coli.